2011
DOI: 10.1021/jf1035542
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Synthesis Inhibitors from Balanophora fungosa

Abstract: Tyrosinase, trypsin, and tryptase are known to play important roles in melanin production of human skin. This paper describes the study of the inhibitory effect of Balanophora fungosa on melanin. The 50% EtOH extract obtained from B. fungosa indicated an inhibitory effect on mushroom tyrosinase activity with an IC(50) value of 15 μg/mL. Bioassay-guided fractionation of the active extract resulted in the isolation of four known compounds. Their structures were identified as 1-O-(E)-caffeoyl-3-O-galloyl-4,6-(S)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Balanophorin has been recorded as a secondary metabolite originated from B. elongata [4]. Bioactivity studies have revealed that isolated compounds of Balanophora species showed antioxidant activity [5]; anti-radical scavenging properties [6][7]; α-glucosidase inhibition [8][9]; cytotoxic toward cancer cell lines, including breast (MCF7), liver (HepG2), lung (SK-LU-1), and epidermal (KB) cancer [5]; xanthine-oxidase inhibition [10]; trypsin and tryptase inhibition [11]; vasodilator [12]; and HIV-1 Env Pseudovirus inhibition [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Balanophorin has been recorded as a secondary metabolite originated from B. elongata [4]. Bioactivity studies have revealed that isolated compounds of Balanophora species showed antioxidant activity [5]; anti-radical scavenging properties [6][7]; α-glucosidase inhibition [8][9]; cytotoxic toward cancer cell lines, including breast (MCF7), liver (HepG2), lung (SK-LU-1), and epidermal (KB) cancer [5]; xanthine-oxidase inhibition [10]; trypsin and tryptase inhibition [11]; vasodilator [12]; and HIV-1 Env Pseudovirus inhibition [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,6,8-10]. Aside from those, the galloyl, HHDP and their derivatives linking the glucosyl unit at C(1), C(3), C(4) and / or C(6) positions through ester bonds are major constituents in the genus Balanophora [1,2,11-18]. …”
Section: Introductionmentioning
confidence: 99%
“…As for the HHDP groups, it was mostly joint to C(4) and C(6) [1,5,7,14,16-18]. Compounds 28–30, isolated from the plants B .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of the synthesis of melanin using Lespedeza cyrtobotrya [11], Lespedeza floribunda and Balanophora fungosa [12] atoms before and after the formation of new bonds during the chemical reactions. The reactants as well as products have been assessed based on the potential energy surfaces (PES) and the geometry corresponding to the global minimum of the PES was considered for further calculations for each molecule.…”
Section: Introductionmentioning
confidence: 99%